Common Effluent Treatment Plants Monitoring and Process Augmentation Options to Conform Non-potable Reuse - Ali, Muntjeer; Almohana, Abdulaziz Ibrahim; Alali, Abdulrhman Fahmi; Kamal, Mohab Amin; Khursheed, Abbas; Khursheed, Anwar; Kazmi, A. A. (Frontiers in Environmental Science, 2021)
The stringency in effluent discharge and reuse standards has made it extremely expensive to discharge the effluents safely or reuse them. Therefore, existing wastewater treatment plants should be evaluated and improved or augmented. With this aim five existing common effluent treatment plants (CETPs) of North India, namely; 4.5 MLD SIDCUL Haridwar; 55 MLD (two streams of 25 and 30 MLD each) at IMT Manesar Gurgaon; 12MLD LRIA, Delhi; 12MLD MIA, Delhi; and 4MLD IIE SIDCUL Pantnagar were evaluated. These plants were designed to produce treated effluent for non-potable reuse. Results showed that the actual integrated efficiency (IEa) of all CETPs was 10-20% larger than standard integrated efficiency (IEs), indicating the suitability of the technology except 12MLD MIA CETP whose IEa was 20% lower than IEs, due to the absence of any biological unit in the process. Combined post treatment of secondary effluent by coagulation, UF, followed by ozonation for CETP SIDCUL Haridwar, was also conducted for its non-potable water reuse. This process was able to reduce BOD by 77%, COD by 76%, turbidity by 96% and TSS by 100%, and all these parameters were conforming the effluent standards for non-potable reuse. The color was reduced to 42 from 88 Pt-Co units by the exposure of wastewater to ozone up to four minutes which reduced the color by 52.3 %, and found within reuse standards.